BER improvement for multi-gigabits-per-second free space optical communications by stabilizing the decision threshold level - Hitam, Salasiah; Abdullah, Mohamad Khazani; Wan Adnan, Wan Azizun; Sheikh Naimullah, Bibi Sarpinah (Federation of Engineering Institutions of Islamic Countries, 2008)
A new transmission and detection technique namely Double Carrier Modulation/Differential Detection (DCM/Diff.D) for free space optical (FSO) is proposed. The technique employs two beams, one modulated with the data, the other with the inverted version of the same data. A differential detection technique is used at the receiver whereby the inverted data are used as the reference to perform the decision making, as opposed to the fixed threshold used in conventional technique. The probability of error under threshold instability in DCM/Diff.D technique and Intensity Modulation/Direct Detection (IM/DD) technique, is compared. A simulation under heavy rainfall condition of 8.33x10-4 cm/sec at bit rate of 2.5 Gbps with 0 dBm of optical transmitter power shows that this technique achieves an improvement of more then twice of distance of the conventional IM/DD.